Effects of Compressive Myofascial Release of Vastus Lateralis on Lateral Patellar Tracking in Patients with Knee Osteoarthritis : Effect of Compressive Myofascial Release on Lateral Patellar Tracking - Batool, Rubia; Amjad, Fatima; Khan, Lal Gul; Ali, Sajjad; Arshad, Anees; Bashir, Kiran (Pakistan Journal of Health Sciences, 2023)
Knee osteoarthritis is highly prevalent around the world and 4th leading cause of disability. Lateral patellar tracking is a common complain of knee osteoarthritis. It causes Q-angle at knee joint to increase that further leads to gait abnormalities. Objective: To determine the effect of compressive myofascial release of vastus lateralis on lateral patellar tracking in terms of pain, range of motion, and functional disability in patients with knee OA. Methods: This Randomized controlled trial was conducted at the Ahad Medicare Clinic and Physiotherapy Centre, Rawalpindi, spanning from December 2020 to June 2021. In this study, 52 participants were carefully selected using the Open Epi software. These individuals were aged 50 years and above and had previously been diagnosed with Grade 2-3 knee osteoarthritis. Participants were then evaluated for the presence of lateral patellar tracking by measuring Q-angle. After meeting eligibility criteria participants were divided into two groups: the Experimental group (n=26) and the Control group (n=26). Numeric Pain Rating Scale (NPRS), Goniometer, and Western Ontario and McMaster Universities Arthrosis Index (WOMAC) were used to take measurements at baseline and at 15 days follow-up. Results: Statistical analysis revealed a significant difference (p<0.05) between the Experimental and Control groups in terms of pain reduction and knee extension range of motion (ROM). Conclusions: The study’s findings revealed that the experimental group exhibited more significant improvements in pain reduction and knee extension compared to the conventional treatment group.